2004
DOI: 10.1161/01.atv.0000148007.06370.68
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Transplantation Reveals That Absence of Macrophage CD36 Is Protective Against Atherosclerosis

Abstract: Objective-CD36 is expressed on multiple cell types and has numerous functions, a subset of which can impact on atherogenesis.In previous work, we demonstrated that CD36 absence was protective against lesion formation. The current objective was to determine whether absence of macrophage CD36 alone was protective. Methods and Results-Lethal irradiation and stem cell transfer were used to create chimeric mice that did or did not express macrophage CD36 in the context of the Apo E-null model of atherosclerosis. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 37 publications
5
109
2
3
Order By: Relevance
“…Male but not female mice also had significantly reduced lesion area at the level of the aortic sinus on a normal chow diet . Using a bone marrow transplant approach, we showed that absence of CD36 in hematopoietic cells accounted for the protection observed in the apoE KO model (Febbraio, Guy, & Silverstein, 2004). This study was again using a 12 week Western diet regimen.…”
Section: Cd36 and Insulin Resistancementioning
confidence: 66%
“…Male but not female mice also had significantly reduced lesion area at the level of the aortic sinus on a normal chow diet . Using a bone marrow transplant approach, we showed that absence of CD36 in hematopoietic cells accounted for the protection observed in the apoE KO model (Febbraio, Guy, & Silverstein, 2004). This study was again using a 12 week Western diet regimen.…”
Section: Cd36 and Insulin Resistancementioning
confidence: 66%
“…Expression of the type B macrophage scavenger receptor CD36 (24) was also attenuated in diabetic RAGE Ϫ/Ϫ /apoE Ϫ/Ϫ mice. Although this change is likely to be secondary to reduced leukocyte recruitment, CD36 has been clearly demonstrated to play a proatherogenic role because the absence of macrophage CD36 protects against vascular lesion formation in mice (25). Thus, one cannot exclude that some of the antiatherosclerotic effects seen with RAGE deletion could be related to changes in the expression of CD36.…”
Section: Diabetes Vol 57 September 2008mentioning
confidence: 99%
“…There are reports suggesting that it reduces atherosclerosis in ApoE [91,92] or LDLR null mice [93,94] although others did not detect significant effects in another model of murine atherosclerosis (ApoE3 Leiden) [95]. CD36-deficient macrophages are more resistant to foam cell formation as shown in ApoE knockout mice [96,97] and by using CD36 blocking antibodies [98]. Moore and colleagues showed that the lack of SR-A or CD36 results in decreased lipid accumulation in peritoneal macrophages whilst associated with increased lesion areas in ApoE null background [99].…”
Section: Uptake Of Modified Ldl By Pattern Recognition Receptorsmentioning
confidence: 99%